(untitled) (Journal of the College of Education for Women, 2019)
The research aims at: Identifying the problems facing kindergarten teachers. Identifying the nature of the problems facing kindergarten teachers. To achieve the aim of the research, the researcher prepared a questionnaire to identify the problems that face the teachers of kindergartens. The questionnaire was subjected to the consultation of a group of specialized expertise in the educational and psychological sciences to certify the propriety of the items of the questionnaire and it gained a rate of (80%), and the stability of the scale gained (0.91) and it stands for a correlation parameter with a statistical significance and it was calculated by using Person’s R Correlation. The sample of the research contained (118) teachers of Kindergartens in Baghdad City including its two sides of Al Karkh and Al Rusafah. The research has come up with the result that 20 problems have been spread in kindergartens that the teachers were suffering of. It has been recognized that the first item of the shortage in games and playing tools got a probable means of (2.761) and a percentage weight of (92.033 %) and the last item of having the parental indifference of supporting the essential daily tools and needs of the child in his bag gained a a probable means of (1.8) and a percentage weight of (60 %).